Hierarchical Type-2 Fuzzy Aggregation of Fuzzy Controllers - Cervantes, Leticia; Castillo, Oscar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book focuses on the fields of fuzzy logic, granular computing and also considering the control area. These areas can work together to solve various control problems, the idea is that this combination of areas would enable even more complex problem solving and better results. In this book we test the proposed method using two benchmark problems: the total flight control and the problem of water level control for a 3 tank system. When fuzzy logic is used it make it easy to performed the simulations, these fuzzy systems help to model the behavior of a real systems, using the fuzzy systems fuzzy rules are generated and with this can generate the behavior of any variable depending on the inputs and linguistic value. For this reason this work considers the proposed architecture using fuzzy systems and with this improve the behavior of the complex control problems.
Theory and Background -- Control Problem and Proposed Method -- Simulation Results -- Conclusions.
Keywords: Computational intelligence; Artificial intelligence; Control engineering; Logic design; Computational Intelligence; Artificial Intelligence; Control and Systems Theory; Logic Design